Microvascular autologous transplantation of partial submandibular gland for severe keratoconjunctivitis sicca. Issue 9 (28th June 2013) - Qin, Jian; Zhang, Lei; Cai, Zhi-gang; Mao, Chi; Liu, Xiao-jing; Lv, Lan; Zou, Liu-he; Peng, Xin; Su, Jia-zeng; Wu, Jun; Yu, Guang-yan
Abstract : Objective: To evaluate the feasibility of microvascular autologous transplantation of partial submandibular gland (SMG) to prevent or reduce epiphora in severe keratoconjunctivitis sicca (KCS). Methods: A total of 39 patients with KCS, covering 42 eyes, were randomised to undergo transplantation of partial or total SMG from January 2006 to December 2009. Clinical data of survival rate of transplanted SMG, ophthalmologic features of best-corrected visual acuity, Schirmer test results, break-up time (BUT) of tear film, fluorescence staining, incidence of postoperative epiphora and frequency of subsequent surgery were compared between two groups. Results: Total SMG transplantation was performed in 22 eyes, and partial SMG transplantation was performed in the other 20 eyes. All transplanted SMGs survived. Microvascular crisis occurred in one case of partial SMG transplantation, but the gland survived after exploration to remove the venous thrombus. Obstruction of the ductal orifice in one case of partial SMG transplantation was resolved by reconstruction of the ductal orifice. Symptoms of dry eyes disappeared, and patients were able to discontinue use of artificial tears. Severe epiphora occurred in 6 eyes undergoing partial SMG transplantation and in 19 eyes undergoing total SMG transplantation (p<0.01). Surgical reduction was performed in 6 eyes undergoing partial SMG transplantation and 18 eyes undergoing total SMG transplantation (p<0.01). Conclusions: Microvascular transplantation of partial SMG is feasible and effective for severe KCS and does not decrease the survival rate of transplanted SMG. For ample SMGs with normal function, transplantation of partial SMG alleviates the symptoms of dry eye and significantly reduces the incidence of severe postoperative epiphora.